Assessment of selected physicochemical parameters and natural radionuclides in Kelantan's well water / Wan Noorhayani Wan Rosdi - Wan Rosdi, Wan Noorhayani (2016)
Well water is groundwater that occurs beneath the water table and one of the important drinking water sources for Kelantanese. The residents in Kelantan, especially those in rural and remote areas are highly depending on groundwater as their drinking water and domestic use, which are mainly located within acid intrusive igneous rock that reported to contain high concentrations of natural occurring radioactive materials (NORMs). A study was conducted with the aim to determine and assess the water quality parameters: Ca2+, Na+, K+, CI", SO42", U, Th and 40K in the water resources. Well water samples (dug wells and bore wells) were collected from 48 locations in 10 districts of Kelantan. In situ measurement were performed to determine basic physicochemical parameters of the water samples; pH, TDS, DO, salinity, conductivity and temperature. The concentrations of Ca2+, Na+ and K+ were determined using Energy Dispersive X-ray Fluorescence (EDXRF) while the concentrations of CI", SO4 " were determined using Ion Chromatography (IC). U and Th were determined using Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). The variations of these results were due to the different geological formations and different surrounding areas of the groundwater systems. The source of the cations are mainly contributed by natural sources such as calcite, feldspar and ion exchange process, while most of the anions are from anthropogenic sources (domestic sewage waste, fertilizer, atmospheric pollution). Based on the basic parameters measured, the pH values (4.7 - 8.1) of well water were not comply with the permissible limit given by MOH and WHO. The turbidity values ranged from 0.3 to 52.7 NTU and also were not comply with the permissible limit given by MOH and WHO. From the activity concentrations of the NORMs, the annual ingestion dose of the natural radioactive materials is lower than WHO recommended value. The various sources of the chemicals in the groundwater systems were classified using PCA. Four principal components were extracted that covered 77.12% of the total variance. The results indicate that K+ and 40K, are from the same sources. Similarly for the U and Th that are from granite rock, CI" and SO42" are from anthropogenic sources and Ca2+ from calcite rock materials.